008 STATE OF RHODE ISLAND, & R. IN GENERAL ASSEMBLY. AN ACT PROHIBITING SMOKING IN CERTAIN PUBLIC PLACES. (Tufts Archival Research Center, 2007)
Marginalia; Draft; Illegible/Difficult to Read; Draft of Rhode Island act prohibiting smoking in certain public places. Cites dangers of second hand smoke as reason for act. Lists places where smoking is prohibited. Discusses penalties of violating the act.